2014
DOI: 10.1021/ie5018805
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Synthesis Using Shielded Sliding Discharge: Effect of Oxygen Content and Positive versus Negative Streamer Mode

Abstract: A shielded sliding discharge reactor operated with nanosecond pulsed power produced ozone with an increased energy yield and in concentrations comparable to commercially available ozone generators. The ozone concentration from air was 4 to 13 g/Nm 3 with an energy yield of 110 to 75 g/kW•h in negative streamers and 4 to 9 g/Nm 3 with an energy yield of 65 to 40 g/kW•h in positive streamers. As the oxygen content in the feed gas was gradually increased, the ozone concentration and energy yield increased, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Rates of the ozone formation reactions increase with specific input energy, which leads to an increase of ozone concentration. Simultaneously, part of the energy injected into the reactor could be converted into heat to raise the temperature in the plasma zone, favoring the following reactions which cause a decrease of ozone concentration: According to the experimental results, it can be concluded that the negative effect of heating is not playing the major role for ozone formation in the range of energy density investigated in the present study.…”
Section: Results and Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Rates of the ozone formation reactions increase with specific input energy, which leads to an increase of ozone concentration. Simultaneously, part of the energy injected into the reactor could be converted into heat to raise the temperature in the plasma zone, favoring the following reactions which cause a decrease of ozone concentration: According to the experimental results, it can be concluded that the negative effect of heating is not playing the major role for ozone formation in the range of energy density investigated in the present study.…”
Section: Results and Discussionmentioning
confidence: 65%
“…In the case of the simulated flue gas containing nitrogen and oxygen mixture simulated flue gas, dissociation or excitation of nitrogen molecules leads to additional O radicals: where “*” represents the excited/high energy state. In the present study, several ppm of NO x was produced (in the case absence of NO in the reaction gases).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multichannel DBD, when the energy yield of ozone is 80 g/kWh [26], the ozone concentration is 15 g/m 3 , only 8.3% of this work. For the surface DBD, when the energy yield of ozone is 75 g/kWh, the ozone concentration is 21.1% of this work [27]. In packedbed plasma [28], when the energy yield of ozone is 108 g/kWh, the ozone concentration is 2.65 g/m 3 .…”
Section: 12 X For Peer Reviewmentioning
confidence: 82%
“…On the other hand, the insulating barrier in a SDBD is sandwiched between the two electrodes and the discharge develops along the surface of the dielectric plate. SDBD is widely investigated in different applications, such as airflow control [6], volatile organic compounds (VOCs) removal [7], ozone production [8,9], and bactericidal agents [10]. The ozone, being a powerful oxidant [11], has many applications in industry.…”
Section: Introductionmentioning
confidence: 99%